The Apostolic fathers; ((The Loeb classical library.), 1912)
CONTENTS.-v.1. I Clement. II. Clement. Ignatius. Polycarp. Didache. Barnabas.-v.2. The shepherd of Hermas. The martyrdom of Polycarp. The epistle to Diognetus.